Effects of water injection on reaction temperature and hydrogen production in horizontal co-axial underground coal gasification - Rika Iriguchi; Akihiro Hamanaka; Fa-qiang Su; Takashi Sasaoka; Hideki Shimada; Ken-ichi Itakura; Kazuhiro Takahashi; Jun-ichi Kodama; Gota Deguchi (Scientific Reports, 2024)
Abstract Underground coal gasification (UCG) is process of directly recovering energy as combustible gases such as hydrogen and carbon monoxide by combusting unmined coal resources in situ. During UCG process, the temperature in the gasification zone can exceed 1,300 °C, raising concerns about the potential melting of the steel pipe for oxidant injection. To control the temperature in the gasification zone, the use of water injection as an injection agent can be an option. Injecting water during UCG process serves two purposes: it decreases the temperature in the reaction zone by the endothermic effect of water, and it enhances the production of H2 by the reduction reaction of water. However, injecting excessive amounts of water may lead to a significant decrease in the temperature in the reaction zone, consequently cannot maintain the temperature range required for the UCG reaction. This study discusses the effects of water injection on the temperature of the gasification zone and the product gas by developing a chemical reaction model of UCG using COMSOL Multiphysics® software. The model was developed based on the temperature and produced gas results obtained from laboratory-scale artificial coal seam UCG experiments. Our findings reveal that water injection significantly influences the gasification process, controlling temperature in the reaction zone and promoting H2 production through steam gasification and water-gas shift reactions. Moreover, under the experiment and analysis conditions of this study, it is revealed that water injection up to an H2O/O2 molar ratio of 3.9 can effectively control the temperature of the gasification zone with enhancing H2 production.